The Economic Content of Indicators of Developing Country Creditworthiness. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1996)
This paper analyzes the economic determinants of developing country creditworthiness indicators for over 60 developing countries for the period from 1980 to 1993. Our results indicate that economic fundamentals--the ratio of non-gold foreign exchange reserves to imports, the ratio of the current account balance to GDP, growth, and inflation explain a large amount of the variation in the credit ratings. All developing country ratings were adversely affected by an increase in international interest rates independently of the domestic economic fundamentals. A country's regional location and the structure of its exports (such as whether it is primarily an exporter of fuel products or manufactured products) were also important.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet